Ceutorhynchus Germar (Coleoptera, Curculionidae) as proxy for Eocene core Brassicaceae: first record of the genus from Rovno amber. (March 2022) - Legalov, Andrei A.; Nazarenko, Vitaliy Yu.; Vasilenko, Dmitry V.; Perkovsky, Evgeny E.
Abstract: The beetle Ceutorhynchus is used as a proxy for Eocene core Brassicaceae. The age of Brassicaceae has been strongly debated because their fossil record is scanty. There are four species of Ceutorhynchus inaffectatus species-group known in the Priabonian: Ceutorhynchus zerovae new species in Rovno amber and three in Baltic amber. There are numerous extant members of the group, all of which feed on core Brassicaceae. Together with differentiation of Brassicaceae-feeding Pierinae (Lepidoptera) in the Priabonian, the strong presence of Ceutorhynchus indicates at least an early Priabonian age of core Brassicaceae. The oldest fossil Brassicaceae is not known in the late Eocene of Europe, but was recorded in Montana, dated in some studies as late Oligocene, but recently as Priabonian (34 Ma). Ceutorhynchus zerovae n. sp. is very close to C . electrinus from Baltic amber. UUID: http://zoobank.org/7f10761f-463d-44c5-9eef-bb4697bfb116 .